Evaluation of models for predicting relative viscosity of ultrasound-assisted synthetic water-in-oil emulsions of Brazilian crude oil. Issue 1 (31st December 2020) - Negris, Luana; Simonassi, Petterson; Saidler, Luila A.; Vicente, Maristela A.; Flores, Erico M. M.; Santos, Maria F. P.
Abstract: Emulsions of water-in-oil (W/O) is a very common occurrence in the oil and gas industries. The viscosity and rheological properties of the emulsions are of great interest to the petroleum industry, especially during oil exploitation and transportation. In this study, emulsion dynamic viscosities were measured (20 °C–50 °C), and rheological profiles were modeled according to Ronningsen, ASTM D-341, Farah, and other viscosity models . Also, a methodology for producing water-in-oil emulsions using ultrasound energy was proposed, and the generated emulsion properties were compared with relevant literature. Emulsions were prepared with 22.3° API crude oil without surfactants. A 400 W ultrasound generator was used for sonication at 24 kHz, and the effects of sonication time and ultrasound amplitude on dynamic viscosity and droplet size distribution were investigated. The emulsions generated by ultrasound sonication showed stability and homogeneity, and droplet size distribution of D 0.5 =0.10 µm and D 4.3 =0.37 µm. The rheological profiles strongly depended on emulsion viscosity and water volumetric fraction. The water volumetric fraction was shown to be the most important factor, the viscosity increased as volumetric fraction increase, while temperature increase led to a viscosity decrease. The experimental results were well fitted by the model proposed by Farah with a 5.5% error. Graphical Abstract: uf0001